Prevalence and co-prevalence of comorbidities among Chinese adult patients with type 2 diabetes mellitus: a cross-sectional, multicenter, retrospective, observational study based on 3B study database - Ji, Qiuhe; Chai, Shangyu; Zhang, Ruya; Li, Jihu; Zheng, Yiman; Rajpathak, Swapnil (Frontiers in Endocrinology, 2024)
Purpose This study aimed to investigate the prevalence and co-prevalence of comorbidities among Chinese individuals with type 2 diabetes (T2DM). Methods Medical records were retrospectively retrieved from the 3B Study database, which provided a comprehensive assessment of comorbid conditions in Chinese adult outpatients with T2DM. Patient characteristics, laboratory measures, and comorbidities were summarized via descriptive analyses, overall and by subgroups of age (<65, 65–74, 75 years) and gender. Results Among 25,454 eligible patients, 53% were female, and the median age was 63 years. The median time of diabetes duration was 6.18 years. A total of 20,309 (79.8%) patients had at least one comorbid condition alongside T2DM. The prevalence of patients with one, two, three, and four or more comorbid conditions was 28.0%, 24.6%, 15.6%, and 11.6%, respectively. Comorbidity burden increased with longer T2DM duration. Older age groups also exhibited higher comorbidity burden. Females with T2DM had a higher overall percentage of comorbidities compared to males (42.7% vs. 37.1%). The most common comorbid conditions in T2DM patients were hypertension (HTN) in 59.9%, overweight/obesity in 58.3%, hyperlipidemia in 42.0%, retinopathy in 16.5%, neuropathy in 15.2%, cardiovascular disease (CVD) in 14.9%, and renal disease in 14.4%. The highest co-prevalence was observed for overweight/obesity and HTN (37.6%), followed by HTN and hyperlipidemia (29.8%), overweight/obesity and hyperlipidemia (27.3%), HTN and CVD (12.6%), HTN and retinopathy (12.1%), and HTN and renal disease (11.3%). Conclusion The majority of T2DM patients exhibit multiple comorbidities. Considering the presence of multimorbidity is crucial in clinical decision-making. Systematic review registration https://clinicaltrials.gov/, identifier NCT01128205.